Effects of limb regeneration on molt, growth and related gene expression in Chinese mitten crab (Eriocheir sinensis) - YUE Wucheng; CHEN Jiao; CI Yuanji; HUANG Shu; WANG Jun; WANG Chenghui (浙江大学学报. 农业与生命科学版)
Limb regeneration is a regrowth phenomenon when limbs of animals are truncated by external forces or self-cut in response to predation, which is a self-protection mechanism formed during the long-term evolution process. Currently, amphibians with tails, and crustaceans belonging to arthropods were intensively studied. The results indicated that the feeding ability, growth and development were greatly affected by regeneration. Molting could be accelerated and the ovary development could be promoted by limb regeneration, inducing expression of the related genes. Chinese mitten crab (Eriocheir sinensis) has the ability of limb regeneration like other crustaceans in its life cycle. However, the molecular mechanism of regeneration for E. sinensis was still unclear. Therefore, study on limb regeneration of E. sinensis can supplement basic biological knowledge for Chinese mitten crab, and provide practical guidance for development of aquaculture industries.A total of 80 juvenile Chinese mitten crabs (40 males and 40 females) were randomly sampled to autotomy treatments with four walking legs (the first and third legs on the left, the second and fourth legs on the right), and the same number of male and female individuals were employed as the control group without any treatment (intact crab). They were separately reared in forty tanks with each of 60 L for two molt cycle, and two crabs with cut limbs (one male, one female) and two intact crabs (one male, one female) were kept in each tank. Body mass, carapace length and carapace width were measured and recorded at the initial stocking stage, and 48 h after the first and second molting, respectively. Meanwhile, the eyes and muscle tissues (regeneration limbs and intact limbs) were collected quickly after the second molt and were stored at -80℃ for quantitative real-time polymerase chain reaction (qRT-PCR) analysis of myostatin gene MSTN, insulin-like growth factor-2 gene IGF2, molting hormone receptor gene EcR, retinoid X receptor gene RXR, and molt-inhibiting hormone gene MIH.The results showed that limb regeneration rate was only 7.6% after the first molt, but reached 91.6% after the second molt; the survival rates of the amputated crabs and intact crabs were roughly equal. Longer inter-molting days (P<0.05) were observed for the amputated crabs than intact crabs, and the body mass-gaining rate was higher than intact crabs (P<0.05) after the first molting. Shorter inter-molting days (P<0.05) were observed for amputated crabs than intact crabs, and no significant difference (P>0.05) was observed for the body mass-gaining rate of the amputated and intact crabs after the second molting. Overall, there was no significant difference of average inter-molting days between the amputated and intact crabs after the two molting. The related gene expression analysis indicated that there were no significant difference (P>0.05) between the amputated and intact crabs in IGF2, RXR and MIH genes. However, there were significant higher expression (P<0.05) of EcR gene and lower expression of MSTN gene for amputated crabs (P<0.05) than the intact crabs.In conclusion, Chinese mitten crab can regenerate new legs in two molt cycles; there are no significant differences on the survival rate, mass-gaining rate and molt cycles between the amputated and intact crabs. The EcR and MSTN genes play important roles in promoting the leg regeneration, and the amputated crab can be kept for further aquaculture.